2011
DOI: 10.1111/j.1365-2702.2010.03525.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of the effect of music therapy and verbal relaxation on chemotherapy‐induced anxiety

Abstract: Prior to chemotherapy, patients with high state anxiety must be sorted from all patients as they are more responsive to interventions. Oncology nurses can offer music and verbal relaxation as adjuvant interventions to reduce chemotherapy-induced anxiety and enhance the quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 52 publications
5
95
0
13
Order By: Relevance
“…The study found that before verbal relaxation to the intervention group, the anxiety level reached the mean and standard deviation of 41.07 (13.71) and after verbal relaxation the anxiety level obtained the mean and standard deviation of 31.63 (10.96), with p value 0,001 [8]. This study was also related to the study of Sepasi, N et al [9].…”
Section: Discussionsupporting
confidence: 69%
“…The study found that before verbal relaxation to the intervention group, the anxiety level reached the mean and standard deviation of 41.07 (13.71) and after verbal relaxation the anxiety level obtained the mean and standard deviation of 31.63 (10.96), with p value 0,001 [8]. This study was also related to the study of Sepasi, N et al [9].…”
Section: Discussionsupporting
confidence: 69%
“…Among other alterations, anxiety causes increased blood pressure, heart rate and respiratory rate (4) . Thus, we can infer that prayers can reduce the intensity of anxiety, blood pressure and respiratory rate levels of patients.…”
Section: Discussionmentioning
confidence: 99%
“…descritOres Musicoterapia; Ansiedade; Neoplasias de Cabeça e Pescoço; Humanização da Assistência; Enfermagem Oncológica. symptoms and vital parameters; mainly in blood pressure, heart rate and chemotherapy (28) , and after radical mastectomy surgery (29) . All health professionals need to be aware of the many effective strategies they can implement to enhance patients' quality of life, whether through music, effective interpersonal communication or other methods in order to improve health outcomes and the provision of care in a safe manner.…”
Section: Discussionmentioning
confidence: 99%